Trajetórias identitárias de professores migrantes em movimento pendular em Sergipe - Alves Neto, Eduardo (2024)
In this study on the Sociology of Migration, the focus is on the identity trajectories of migrant teachers in pendular movement in the State of Sergipe, Brazil. The research explores how pendular migration affects the construction of the professional and personal identities of these educators, emphasizing identity negotiation and the social, cultural, and identity repercussions of this phenomenon. The general objective is to understand the dynamics and challenges faced by teachers in their daily commutes, highlighting the importance of temporality and the processes of identity formation and transformation. It is justified by the need to deepen the understanding of the impact of pendular migration on the trajectories and identities of teachers in Sergipe, a region little explored in this context, thus filling a significant gap in the existing literature. The methodology adopted is Oral History, with semi-structured online interviews complemented by written sources, allowing for a profound analysis of migratory experiences. The results indicate that pendular migration significantly influences the identities and practices of teachers, revealing challenges related to displacement and work conditions. Employment stability and vocation emerge as the main reasons for remaining in the teaching profession, while adaptation strategies and the formation of support networks are crucial. This work contributes to a deeper understanding of the pendular migration phenomenon and its implications.